Implementation Of Legal Protection Of Children Who Become Victims Of Criminal Action Sexual Violence In Jombang District - Suwandi Suwandi (Veteran Justice Journal, 2019)
This research aims to find out the implementation of criminal protection against child victims of criminal acts against child victims of sexual violence in Jombang District. This research uses empirical juridical methods, namely research in the form of empirical studies to find theories regarding the implementation of legal protection for children who are victims of criminal acts of sexual violence in Jombang. Data sources were obtained from literature, applicable legislation and interviews with the Protection Unit for Women and Children at the Jombang Regional Police. Analysis of the data used is a qualitative approach to primary data and secondary data. The results of the study can be concluded that the implementation of legal protection provided by the Jombang Regional Police Unit for children who are victims of criminal acts of sexual violence is to conceal the identity of the victim, provide counseling outside the legal channels, conduct investigations, provide a Notification of the Progress of Investigation (SP2HP), cooperating with Non-Governmental Organizations (NGOs).